Describing the Linkages of the Citizenship and Immigration Canada Permanent Resident Data and Vital Statistics-Death Registry to Ontario's Administrative Health Database. (2017) - Guttmann, Astrid; Chiu, Maria; Lebenbaum, Michael; Lam, Kelvin; Chong, Nelson; Azimaee, Mahmoud; Iron, Karey; Manuel, Doug
No abstract available